Edukasi Siswa melalui Pengenalan Profesi Apoteker pada Program Kelas Inspirasi di SDN Parinring Makassar - Awaluddin, Nurhikma; Awaluddin, Akbar (LP2M INSURI Ponorogo, 2023)
Pharmacists are the source of information about drugs, but many people still need to familiarize themselves with the pharmacist profession. This causes problems for children as well as adults who lack knowledge about medicines in children, which can lead to drug abuse. This activity aims to educate elementary school students about the introduction of the pharmacist profession, an introduction to drugs, and to foster curiosity about the pharmacist profession from an early age. This activity was carried out at SD Negeri Parinring, Kec: Manggala, Makassar, with 35 participants from grade 6 elementary school students. The Participatory Rural Appraisal (PRA) model is used in community service activities, promoting community empowerment to participate. The action begins with an introduction to material delivered by pharmacists. After that, sing the pharmacist's jingle, and give questions to test the extent of drug knowledge possessed by elementary school students, the results of this community service, especially at SD Negeri Parinring, Kec. Manggala, Makassar can increase understanding and drug awareness early to minimize unwanted side effects and become an agent of change who can explain the confusion of drug information circulating among students.